Analisis Peran Syaykh Al-Zaytun dalam Pendidikan Toleransi di Mahad Al-Zaytun - Anida Atulloh Hanifa; Siti Ngainnur Rohmah; Iwan Iwan; Fadilah Al-Madani; Badriyono Badriyono (Karakter : Jurnal Riset Ilmu Pendidikan Islam, 2024)
This study explores the contribution of Shaykh Al-Zaytun in shaping Mahad Al-Zaytun as a school that promotes pluralism and diversity. The aim is to provide a better understanding of how Islamic education can adapt to modern society without the need for esoteric evidence. This study also uses Pustaka methodology to identify theories related to tolerance and tolerance, as well as literature relevant to developing a culture of tolerance through education at Mahad Al-Zaytun. This study also uses a case study approach to examine the influence of Shaykh Al-Zaytun on the modern Islamic education system. This study focuses on the school's vision and the committee's commitment to tolerance. This study also highlights the potential for collaboration with other institutions, both local and international, to strengthen tolerance education. This study concludes by highlighting the importance of Shaykh Al-Zaytun's transformational leadership in promoting tolerance in everyday life.